Using infrared thermometry to manage irrigation water for some vegetable crops - Mahmoud, Amr K. (Agriculture and Natural Resources, 2022)
Measurement of the canopy temperature using infrared thermometry has been extensively studied to understand plant water status and to schedule crop irrigation. Many regions globally have insufficient water supply resulting in reduced crop yields. Thus, this work investigated the best treatments to cultivate kohlrabi using three amounts of water during growth (T1 = 180 mm; T2 = 270 mm; T3 = 360 mm) and three distances between plants (S1 = 0.50 m; S2 = 0.75 m; S3 = 1.00 m). The amount of water was estimated related to canopy temperature (Tc), air temperature (Ta) and vapor pressure deficit (VPD). The results indicated that there was an inverse relationship between Tc and water quantities, where Tc decreased 3ºC from 28ºC to 25ºC under T3 compared to T1. Furthermore, VPD was (2.18 KPa) under T1 and S3, with Tc – Ta equal to 1.6ºC. VPD decreased from 1.78 KPa to 1.64 KPa when the leaf area index (LAI) increased from 0.6 m2/m2 to 1.2 m2/m2 for T2. Thus, the highest yield (4,540 kg/fed) was observed with T2 when the VPD of the kohlrabi flower stage was 1.73KPa and Tc – Ta was -0.453°C. Clearly, by increasing the distance between plants from 0.5 m to 1.0 m, the yield decreased (233.5 kg/fed). Finally, the models VPD = 1.826 + [0.00752 × LAI] + [0.2058 × (Tc – Ta)] and T = 45.1704 – [16.213 × VPD] indicated that the total water applied (T) for kohlrabi depended on four parameters (LAI, Tc, Ta and VPD).